Impact and explosion cratering: planetary and terrestrial implications - Symposium on Planetary Cratering Mechanics (1976 : Flagstaff, Ariz); Pepin, R. O.; Merrill, R. B.; Roddy, D. J.; Lunar Science Institute; United States. Geological Survey. Branch of Astrogeologic Studies (New York: Pergamon, 1977)
26